1970
DOI: 10.1126/science.169.3950.1042
|View full text |Cite
|
Sign up to set email alerts
|

A Theory of Self-Nonself Discrimination

Abstract: 1) Induction of humoral antibody formation involves the obligatory recognition of two determinants on an antigen, one by the receptor antibody of the antigen-sensitive cell and the other by carrier antibody (associative interaction). 2) Paralysis of antibody formation involves the obligatory recognition of only one determinant by the receptor antibody of the antigen-sensitive cell; that is, a nonimmunogenic molecule (a hapten) can paralyze antigen-sensitive cells. 3) There is competition between paralysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
297
3
1

Year Published

1973
1973
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,541 publications
(321 citation statements)
references
References 30 publications
8
297
3
1
Order By: Relevance
“…In this assay, a proliferative response will normally occur in 1-5% of cells as a result of activation through their cell-surface TCR in response to allogeneic MHC (25). CTLA4Ig was able to block proliferation in a dose-dependent fashion with virtually complete inhibition observed at a concentration of 1 have been reported to be inhibited by nonstimulatory Fab' fragments of an anti-CD28 mAb (9). Together, these data suggest that to mount a proliferative response in vitro, alloreactive T cells must be stimulated not only through MHC engagement of the TCR but also through costimulation of the CD28 receptor by B7 engagement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this assay, a proliferative response will normally occur in 1-5% of cells as a result of activation through their cell-surface TCR in response to allogeneic MHC (25). CTLA4Ig was able to block proliferation in a dose-dependent fashion with virtually complete inhibition observed at a concentration of 1 have been reported to be inhibited by nonstimulatory Fab' fragments of an anti-CD28 mAb (9). Together, these data suggest that to mount a proliferative response in vitro, alloreactive T cells must be stimulated not only through MHC engagement of the TCR but also through costimulation of the CD28 receptor by B7 engagement.…”
Section: Resultsmentioning
confidence: 99%
“…However, several studies have demonstrated that signals transduced via the antigen receptor are not by themselves sufficient to lead to complete T-cell activation and proliferation but require a second costimulatory signal (2)(3)(4)(5)(6)(7)(8). It has been hypothesized that this second signal(s) might be provided through one or more co-receptors on T cells interacting with their nonpolymorphic ligands on antigen-presenting cells (2,9). One candidate for this coreceptor activity is CD28, a 44-kDa polypeptide that is expressed on resting T cells as a homodimer.…”
mentioning
confidence: 99%
“…It may be that LPS stimulation of B cells can alter the obligate tolerant state which otherwise results from the binding of tolerogen to specific B cells. In this regard, the phenomenon could be integrated within the two signal model of immunity proposed by Bretscher and Cohn (26) in that specific B-cell stimulation would occur after binding of tolerogen (signal 1) and LPS (signal 2). A similar interpretation (27) has recently been advanced to explain the observation that polymerized flagellin (signal 2) can modulate antibody formation to an otherwise tolerogenic form of deaggregated fowl gamma globulin (signal 1).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supporting the concept that deficient accessory adherent cell function might result in immunologic unresponsiveness when antigen is presented directly to populations of B and T cells has been recently discussed (13). Moreover, when viewed in light of one 2-signal model for B-cell induction and paralysis (14,15) Peyer's patch B cells might be predicted to enter a paralytic pathway since generation of an effective second signal for Bcell induction to most thymus-dependent antigens likely requires the presence of both cooperating T cells and macrophage-like accessory adherent cells (16,17) . However, preliminary in vivo studies in our laboratory showed that SRBC feeding did not reduce the ability to subsequently induce anti-SRBC responses in Peyer's patch cultures and in vitro incubation of Peyer's patch cells with SRBC before the addition of ME did not abolish the anti-SRBC response (M. Kagnoff, unpublished observations) .…”
Section: Discussionmentioning
confidence: 99%